HUBUNGAN KADAR DEBU TERHIRUP DENGAN GANGGUAN FUNGSI PARU PADA PEKERJA INDUSTRI MEBEL PT MARLENY JEPARA - Nabilla Rachma Anjani; Mursid Rahardjo; Budiyono Budiyono (Jurnal Kesehatan Masyarakat (Undip), 2018)
Lung function disorder is one of the most common occupational diseases that cause of morbidity and mortality worldwide. Furniture industry workers are workers with high levels of dust exposure and are at risk of developing lung function disorders. Based on the results of a preliminary study at PT Marleny Jepara showed that the total dust value in 3 parts of furniture production exceeded the quality standards set in the sanding section of 1200.855 μg/Nm3, finishing section 970.085 μg/Nm3, seat section 474.359 μg/Nm3. This research aims to analyze the association of respirable dust exposure and lung function disorders on furniture industry workers of PT Marleny Jepara. This reseacrh was an observasional research with a cross sectional approach. Population of this research were 42 workers with inclusion criteria at furniture industry PT Marleny Jepara, meanwhile the samples were 30 workers by simple random sampling.  Data were analyzed by using Chi Square test with α = 0.05. The results showed there were 82.6% respondents with respirable dust exposure above the TLV had lung function disorder. The most common type lung function of respondents was mild restriction (85.7%). There ware a significants association between respirable dust exposure (p value = 0.014) and lung function disorder. The research can be concluded that the respondents with the respirable dust value above TLV had a greater risk of having lung function disorder.